Transition to adult care in Finnish adolescents with juvenile idiopathic arthritis. (2nd November 2022) - Mikola, K; Rebane, K; Glerup, M; Kautiainen, H; Relas, H; Peltoniemi, S; Aalto, K
Abstract : Objective: The symptoms of juvenile idiopathic arthritis (JIA) and the necessity for continuous treatment may persist in adulthood. Therefore, patients with JIA need to be appropriately transferred to adult care. We aimed to analyse the timing of the patients' transition to adult care, and patients' self-management skills with the process and the quality of the transition. Method: This study included 161 Finnish participants of the population-based Nordic JIA cohort who attended a 17 year follow-up appointment. Special attention was paid to the three groups: those referred by the paediatric rheumatology outpatient clinic to primary healthcare (PHC), those who were directly transferred to adult rheumatology care, and those who were later referred. Results: A total of 136 patients (84%) were eligible to participate in the study, and 40% of them were directly transferred to an adult rheumatology clinic. Of the patients, 72% eventually ended up being referred to an adult rheumatology outpatient clinic. However, 16% of the patients in the PHC group had active disease during the study appointment and were referred to adult services after the study visit. Conclusion: This study reveals the need to improve the transition process from paediatric care to adult care and to find the variables that can indicate the need for immediate transition. Although challenging, it is important to avoid treatment delay in adult patients with JIA who may have active disease but who do not have appropriate access to an adult rheumatological outpatient clinic.